MiR-622 Counteracts the NUAK1-Induced Gastric Cancer Cell Proliferation and the Antioxidative Stress. (14th July 2022) - Yang, Jian; Lu, Jian; Yin, Ni; Sun, Jingyue; Pu, Jianhong; Zang, Jin
Abstract : Background . Gastric cancer (GC), a highly prevalent gastric cancer, has high-risk mortality. Thus, investigating strategies to counteract its growth is important to provide theoretical guidance for its prevention and treatment. It has been pointed out that abnormal expression of microRNAs (miRNAs) serves as noninvasive biomarkers for GC. This present study probed into the role of miR-622 and the NUAK family SNF1-like kinase 1 (NUAK1). Methods . Five mRNA datasets (GSE64916, GSE118916, GSE122401, GSE158662, and GSE159721) and one miRNA dataset (GSE128720) from the Gene Expression of Omnibus (GEO) database were used to analyze the differentially expressed miRNAs and mRNA in GC and noncancer samples. Further, western blot, real-time quantitative PCR (qRT-PCR), reactive oxygen species (ROS) assay kit experiments, and wound healing assay, together with in vivo experiments, were performed. Results . miR-622 was downregulated, and NUAK1 was upregulated in GC, and NUAK1 was a potential target of miR-622. Knocking down NUAK1 decreased GC cell proliferation and migration but increased oxidative stress in vitro and inhibited the development of tumor in vivo, while miR-622 acted to suppress the action of NUAK1 through the miR-622/NUAK1/p-protein kinase B (Akt) axis, thereby inhibiting the occurrence of GC. Conclusion . miR-622 and NUAK1 demonstrated potential for being targets and biomarkers for GC treatment.